2018
DOI: 10.1186/s12866-018-1163-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CTX-M-15 harboring Escherichia coli isolated from wild birds in Tunisia

Abstract: BackgroundThe spreading of antibiotic resistant bacteria is becoming nowadays an alarming threat to human and animal health. There is increasing evidence showing that wild birds could significantly contribute to the transmission and spreading of drug-resistant bacteria. However, data for antimicrobial resistance in wild birds remain scarce, especially throughout Africa. The aims of this investigation were to analyze the prevalence of ESBL-producing E. coli in faecal samples of wild birds in Tunisia and to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 63 publications
5
14
0
Order By: Relevance
“…Isolation of CR-carrying bacteria from wild birds has been globally reported in E . coli [1520] and less frequently in Klebsiella pneumoniae [21]. All these results confirm the dissemination success of ESBL bla SHV-12 and bla CTX-M variants in wild birds worldwide.…”
Section: Introductionsupporting
confidence: 58%
“…Isolation of CR-carrying bacteria from wild birds has been globally reported in E . coli [1520] and less frequently in Klebsiella pneumoniae [21]. All these results confirm the dissemination success of ESBL bla SHV-12 and bla CTX-M variants in wild birds worldwide.…”
Section: Introductionsupporting
confidence: 58%
“…However, most of the environmental-wildlife interface studies have been focused on wild birds, as principal AMR disseminators by their migratory routes, with a limited variety of AMR bacteria species described. Isolation of CR-carrying bacteria from wild birds has been globally reported in Escherichia coli [12-17] and less frequently in Klebsiella pneumoniae [18]. All these results confirm the dissemination success of ESBL bla SHV-12 and bla CTX-M variants in wild birds worldwide.…”
Section: Introductionsupporting
confidence: 57%
“…Studies performed in the Iberian Peninsula in wildlife, have reported bla CTX-M-1 as the main ESBL gene circulating [19,26]. Additionally, bla CTX-M-14a and bla SHV-12 have also been frequently detected in E. coli from wild animals [12,27-29] with bla CTX-M-15 described in a recent study carried out in wild birds in Tunisia [17]. Interestingly, in the present study, bla CTX-M-1 and bla CTX-M-14a were never detected, whereas bla CMY-2, bla SHV- 12 and bla CTX-M-15 were frequently isolated not only in E. coli but also in K. pneumoniae and C. freundii isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic mechanisms have been involved in the spread of ARGs, but conjugation is thought to have the greatest influence [3]. Furthermore, it has been reported that E. coli obtains antimicrobial resistance faster than other microorganisms [4]. It is especially relevant regarding the increase of β-lactam resistance in E. coli due…”
Section: Introductionmentioning
confidence: 99%